Possible directions for using bran in heat-power engineering; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Gaydabrus M. Maria; Razov I. Igor; Tabakaev R. B. Roman Borisovich; Lebedev V. Vitaly (2017, 2017)
Title screen